Dynamic monitoring revealed a slightly prolonged waiting time for total gastrectomy during the COVID-19 pandemic without increasing the short-term complications - Zheng, Xiaohao; Ding, Shikang; Wu, Ming; Sun, Chunyang; Wu, Yunzi; Wang, Shenghui; Du, Yongxing; Yang, Lin; Xue, Liyan; Wang, Bingzhi; Wang, Chengfeng; Cui, Wei; et al. (Frontiers in Oncology, 2022)
We aimed to determine the pattern of delay and its effect on the short-term outcomes of total gastrectomy before and during the coronavirus disease 2019 (COVID-19) pandemic. Overlaid line graphs were used to visualize the dynamic changes in the severity of the pandemic, number of gastric cancer patients, and waiting time for a total gastrectomy. We observed a slightly longer waiting time during the pandemic (median: 28.00 days, interquartile range: 22.00–34.75) than before the pandemic (median: 25.00 days, interquartile range: 18.00–34.00; p = 0.0071). Moreover, we study the effect of delayed surgery (waiting time > 30 days) on short-term outcomes using postoperative complications, extreme value of laboratory results, and postoperative stay. In patients who had longer waiting times, we did not observe worse short-term complication rates (grade II–IV: 15% vs. 19%, p = 0.27; grade III–IV: 7.3% vs. 9.2%, p = 0.51, the short waiting group vs. the prolonged waiting group) or a higher risk of a longer POD (univariable: OR 1.09, 95% CI 0.80–1.49, p = 0.59; multivariable: OR 1.10, 95% CI 0.78–1.55, p = 0.59). Patients in the short waiting group, rather than in the delayed surgery group, had an increased risk of bleeding in analyses of laboratory results (plasma prothrombin activity, hemoglobin, and hematocrit). A slightly prolonged preoperative waiting time during COVID-19 pandemic might not influence the short-term outcomes of patients who underwent total gastrectomy.